Implementasi Total Quality Management Untuk Meningkatkan Mutu Manufacturing Dan Jasa Di PT. Dahana (Persero) Subang - Ayi Astuti; Yosef Abdul Ghani; Oda I.B Haryanto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
Production of PT. Dahana in 2011-2016 continues to increase, 3 main sectors such as services, Drilling & Blasting, Explosive Manufacturig continue to increase. In order to maintain its existence in the service industry and manufacturing explosives, PT. Dahana continues to make improvements on all lines of the company by applying Total Quality Management / integrated quality management. The implementation of quality management emphasizes the needs of service users both at home and abroad. The quality improvements applied to Total Quality Management focus on improving the quality of output, and reducing production costs but productivity and quality are increasing. Based on it is interesting to see the implementation of integrated management system that has been run by the management of PT. Dahana Subang in an effort to maintain its existence increase production in the range of 2011-2016. The method used in this research is qualitative. And the results obtained that the principles of integrated quality management are running well, in addition to the renewal of management system is done with the design of SIMADA (Quality Management System Dahana) for the quality of service and Manufacturing is maintained quality.